1996
DOI: 10.1007/bf01254479
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of dopamine transporters in humans with technetium-99m TRODAT 1

Abstract: Technetium-99m TRODAT-1, a tropane derivative, has shown promise as a tracer for the imaging of dopamine transporters in preliminary studies in rats and baboons. The present report concerns the first study of the use of [99mTc]TRODAT-1 for the same purpose in humans. The specific uptake of [99mTc]TRODAT-1 in dopamine transporter sites located in the basal ganglia area was confirmed: the best contrast between the basal ganglia and the occipital area, which is devoid of dopamine transporters, was achieved at 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(92 citation statements)
references
References 6 publications
1
89
0
2
Order By: Relevance
“…We chose to investigate analogs that incorporate 99m Tc to be used with SPECT as this strategy offers the advantage of widespread availability of 99m Tc and SPECT cameras. To date, the best example of a successful low-molecular weight, 99m Tc-labeled targeted radiotracer is TRODAT1 (36), which images dopamine transporters and has shown promise for the diagnosis of a variety of neurologic disorders (37).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to investigate analogs that incorporate 99m Tc to be used with SPECT as this strategy offers the advantage of widespread availability of 99m Tc and SPECT cameras. To date, the best example of a successful low-molecular weight, 99m Tc-labeled targeted radiotracer is TRODAT1 (36), which images dopamine transporters and has shown promise for the diagnosis of a variety of neurologic disorders (37).…”
Section: Discussionmentioning
confidence: 99%
“…This neuronal loss is more severe in the ventrolateral nigra, projecting mainly to the posterior putamen. Dopaminergic dysfunction in PD has been visualized with positron emission tomography (PET) or single photon emission tomography (SPECT) by using various tracers [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Degeneration of the projection from the substantia nigra to the striatum results in loss of DAT (Kaufman and Madras, 1991). Several studies showed good relationship between DAT concentrations and striatum dopamine level, and the regional concentration of DAT may present the tone of dopaminergic system at that area and is thought to be a marker of dopamine terminal innervations (Mozley et al, 2000;Kung et al, 1996). In recent years, DAT imaging with positron emission tomography (PET) and single photon emission computed tomography (SPECT) has developed into an objective in vivo method to evaluate nigrostriatal neuron loss in PD (Booij et al, 1999;Kung et al, 1996;Asenbaum et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed good relationship between DAT concentrations and striatum dopamine level, and the regional concentration of DAT may present the tone of dopaminergic system at that area and is thought to be a marker of dopamine terminal innervations (Mozley et al, 2000;Kung et al, 1996). In recent years, DAT imaging with positron emission tomography (PET) and single photon emission computed tomography (SPECT) has developed into an objective in vivo method to evaluate nigrostriatal neuron loss in PD (Booij et al, 1999;Kung et al, 1996;Asenbaum et al, 1997). Several results displayed a correlation between overall striatal DAT binding and global measures of the severity of PD such as the Hoehn and Yahr scale (HYS) (Hoehn and Yahr, 1967), the total score on the Unified Parkinson's Disease Rating Scale (UPDRS).…”
Section: Introductionmentioning
confidence: 99%